Hyaluronate nanofabric sheet and its manufacturing method

By combining ultra-low and medium molecular weight hyaluronic acid and processing it through electrospinning using purified water, the hyaluronic acid nanofabric sheet achieves a high percutaneous absorption rate and mechanical strength, addressing the limitations of existing hyaluronic acid films and nanofiber sheets.

JP2025510707AActive Publication Date: 2025-04-15JINWOO BIO
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2024556047
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-06-14
Filing Date
2023-03-23
Publication Date
2025-04-15
Estimated Expiration
2043-03-23

AI Technical Summary

Technical Problem

Existing hyaluronic acid films and nanofiber sheets face challenges in achieving a high percutaneous absorption rate and mechanical properties, particularly due to limitations in molecular weight range, manufacturing complexity, and the need for toxic solvents.

Method used

A hyaluronic acid nanofabric sheet is produced using ultra-low molecular weight hyaluronic acid (5x10^3 ~ 5x10^4 Da) combined with medium molecular weight hyaluronic acid (1x10^5 ~ 1x10^6 Da), dissolved in purified water, and processed via electrospinning to achieve excellent transdermal absorption and mechanical properties.

Benefits of technology

The resulting hyaluronic acid nanofabric sheet exhibits a percutaneous absorption rate of 77.70-86.08% and a tensile strength of 5.32-10.91 MPa, enabling effective skin penetration and robust physical properties suitable for various applications, including skin masks and drug delivery systems.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025510707000001_ABST
    Figure 2025510707000001_ABST
Patent Text Reader

Abstract

The present invention relates to a hyaluronate nanofabric sheet and a method for producing the same, and more particularly to a hyaluronate nanofabric sheet having excellent percutaneous absorption rate and physical properties and a method for producing the same. The method for producing the hyaluronate nanofabric sheet of the present invention comprises: (a) a hyaluronate nanofabric sheet having a weight average molecular weight of 5×10 3 ~5×10 4 Da hyaluronate and weight-average molecular weight 1×10 5 ~1×10 6 The method includes the steps of (a) mixing hyaluronic acid salt of 1000 Da with hyaluronic acid salt of 1000 Da and dissolving it in water to prepare an aqueous solution of hyaluronic acid salt, and (b) electrospinning the aqueous solution of hyaluronic acid salt. The hyaluronic acid salt nanofabric sheet of the present invention is mainly composed of ultra-low molecular weight hyaluronic acid, and has excellent percutaneous absorption rate. In addition, since a certain amount of medium molecular weight hyaluronic acid is mixed, it also has excellent mechanical properties, and therefore can be applied to various applications such as a mask patch for skin topical preparations and a carrier for ophthalmic or mucosal drug delivery systems.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a hyaluronate nanofabric sheet and a manufacturing method thereof, and more particularly to a hyaluronate nanofabric sheet having excellent percutaneous absorption rate and physical properties and a manufacturing method thereof. [Background technology]

[0002] Hyaluronic acid or hyaluronate is uniformly distributed in the connective tissue, epithelium, and nerve tissue of the human body, and is a biocompatible material with various physiological activities that can contain a large amount of water. Since it has excellent viscoelasticity, it has been proven to be effective in regenerating and moisturizing the skin, maintaining elasticity, and improving wrinkles. Recently, there has been a surge in demand for anti-aging cosmetics, foods, medicines, and fillers for medical devices that contain it.

[0003] Currently, most finished products using hyaluronate on the market are in liquid form and contain hyaluronate in a dilute concentration, i.e., the main component is water, not hyaluronate, which limits their use. In addition, due to the low safety of hyaluronate itself against microorganisms, hyaluronate must be manufactured in sterile facilities when used for medicine or medical devices, and preservatives of safety concerns must be used when used for cosmetics.

[0004] Therefore, research is being conducted to solidify hyaluronic acid or hyaluronate salts, such as into films or fibers, rather than into a liquid form.

[0005] Korean Patent Publication No. 2019-0138907 discloses a mask sheet containing a hyaluronic acid film, and Korean Patent Publication No. 2019-0106091 discloses a method for producing a hyaluronate film using a solvent casting or automatic coater casting method.

[0006] However, the manufacturing process for mass production of hyaluronate films is somewhat complicated, and when used as a mask pack, it does not adhere well to the skin or has a low transdermal absorption rate.

[0007] In order to improve the manufacturing process of such hyaluronate films, Korean Patent No. 2338355 discloses a manufacturing method for wet hyaluronate nonwoven fabric that can be used as a cosmetic patch, a wet wound dressing, a tissue adhesion prevention film, etc., and Korean Patent No. 1224882 discloses a nanofiber sheet made of hyaluronic acid. However, Korean Patent No. 2338355 uses hyaluronate with a molecular weight of 50,000 to 100,000 Da, while Korean Patent No. 1224882 uses hyaluronate with a molecular weight of 100,000 to 1,600,000 Da, which causes a problem of low percutaneous absorption rate.

[0008] Hyaluronic acid or hyaluronates are classified into ultra-low molecular weight, low molecular weight, medium molecular weight, and high molecular weight, depending on the molecular weight.

[0009] Medium and high molecular weight hyaluronates have excellent mechanical properties and are therefore easy to manufacture into films, but have difficulty in skin permeation and absorption.In contrast, the lower the molecular weight of hyaluronic acid or hyaluronate, the easier it is to permeate and absorb into the skin, but the lower the mechanical properties and the more difficult it is to manufacture into a film.

[0010] In addition, in the case of hyaluronate, which is a polymeric polysaccharide with many hydroxyl groups in the molecule, the molecule itself is positively charged, which means that there are many limitations to electrospinning. Therefore, in the case of the production of hyaluronate nonwoven fabric by conventional electrospinning (Castro, KC, Campos, MGN, & Mei, LHI (2021). International Journal of Biological Macromolecules, 173, 251-266.), hyaluronic acid nonwoven fabric was produced using alkaline solvents such as sodium hydroxide or potassium hydroxide, or toxic organic solvents (Ewelina, et al. Advances in Polymer Technology 37.6 (2018):1929-1940.), but toxic organic solvents or salts must be used, and there is a risk that these organic solvents or salts will remain after the nonwoven fabric is formed, so there are limitations to its actual use.

[0011] Therefore, the present inventors have endeavored to produce a hyaluronic acid sheet that is easily permeable and absorbed through the skin without adding organic solvents or salts, and has excellent mechanical properties for commercialization. As a result, 4 The main component is ultra-low molecular weight hyaluronic acid (1×10 Da), which has excellent mechanical properties and can be processed for commercialization. 5 ~1×10 6 It was confirmed that a hyaluronate nanofabric sheet with excellent transdermal absorption rate and mechanical properties can be produced by adding a medium molecular weight hyaluronate of Da, dissolving it in water, and then electrospinning the resulting solution, thereby completing the present invention. Summary of the Invention [Problem to be solved by the invention]

[0012] An object of the present invention is to provide a hyaluronate nanofabric sheet having excellent percutaneous absorption rate and mechanical properties.

[0013] Another object of the present invention is to provide a method for producing a hyaluronate nanofabric sheet having excellent percutaneous absorption rate and tensile strength. [Means for solving the problem]

[0014] In order to achieve the above object, the present invention provides a hyaluronate nanofabric sheet consisting of hyaluronate fibers having a diameter of 0.3 to 5 μm, which are produced by electrospinning using a solvent of purified water alone.

[0015] In order to achieve the above object, the present invention provides a hyaluronate nanofabric sheet having a transdermal absorbency of 77.70 to 86.08% and a tensile strength of 5.32 to 10.91 MPa.

[0016] In the present invention, the hyaluronic acid salt has a weight average molecular weight of 5×10 3 ~5×10 4 Da hyaluronate salt 88.9-98.1% by weight, and weight-average molecular weight 1×10 5 ~1×10 6 It is characterized by being composed of 1.9 to 11.1 wt % of hyaluronate of Da.

[0017] In the present invention, the hyaluronate nanofabric sheet is characterized in that it is used as a mask patch for topical skin preparations, or a carrier for ophthalmic or mucosal drug delivery systems.

[0018] The present invention also provides a polymer having a weight average molecular weight of 5×10 3 ~5×10 4 Da hyaluronate and weight-average molecular weight 1×10 5 ~1×10 6 The present invention provides a method for producing a hyaluronate nanofabric sheet, comprising the steps of (a) mixing a hyaluronate having a molecular weight of 1000 to 15000 Da with a hyaluronate having a molecular weight of 10000 Da and dissolving the mixture in water to produce an aqueous hyaluronate solution; and (b) electrospinning the aqueous hyaluronate solution.

[0019] In the present invention, the viscosity of the aqueous hyaluronate solution is characterized by being 1,000 to 15,000 cPs. Effect of the Invention

[0020] The hyaluronate nanofabric sheet of the present invention is composed primarily of ultra-low molecular weight hyaluronic acid, and not only has excellent percutaneous absorption rate, but also has excellent mechanical properties because it contains a certain amount of medium molecular weight hyaluronic acid mixed in. [Brief description of the drawings]

[0021] [Figure 1] Photographs of hyaluronate nanofabric sheets prepared by an electrospinning method according to an embodiment of the present invention (A: nanofiber-type sheet, B: dot-type sheet, C: micrograph of nanofiber-type sheet, D: micrograph of dot-type sheet). [Diagram 2] 1 is a photograph of a transmission experiment using a fluorescent microscope of a hyaluronate nanofabric sheet prepared according to an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0022] In the present invention, "hyaluronate nanofabric sheet" means a sheet containing nano-hyaluronate fibers produced by electrospinning.

[0023] Hyaluronic acid or hyaluronates with a lower molecular weight are more easily permeated and absorbed through the skin, but this has the problem that it is difficult to produce a sheet with high physical properties by electrospinning.

[0024] Korean Patent No. 2338355 uses hyaluronate with a molecular weight of 50,000-100,000 Da to manufacture hyaluronate nonwoven fabric, and Korean Patent No. 1224882 uses hyaluronate with a molecular weight of 100,000-1,600,000 Da to manufacture hyaluronate nanofiber sheet. These products use high molecular weight hyaluronate, so they use alkaline solvents such as sodium hydroxide and potassium hydroxide to reduce viscosity, which causes problems such as low percutaneous absorption and the inability to properly deliver various physiological activities of hyaluronate to the skin.

[0025] In the present invention, 5 × 10 3 ~5×10 4 1×10 Da of ultra-low molecular weight hyaluronic acid 5 ~1×10 6 It was confirmed that when Da medium molecular weight hyaluronate was added, it was possible to mass-produce uniform hyaluronate nanofabric sheets that not only had excellent percutaneous absorption rate but also had excellent mechanical properties that made them processable.

[0026] In the present invention, ultra-low molecular weight hyaluronate and medium molecular weight hyaluronate were mixed, and then dissolved in purified water without adding an alkaline solvent to produce a hyaluronate aqueous solution with a viscosity of 1,000 to 15,000 cPs (25°C). The solution was then electrospun to produce a hyaluronate nanofabric sheet.

[0027] As a result, it was possible to mass-produce hyaluronate nanofabric sheets, and it was confirmed that the transdermal absorption rate of the produced hyaluronate nanofabric sheets was 77.70 to 86.08%.

[0028] Therefore, in one aspect, the present invention relates to a hyaluronate nanofabric sheet consisting of hyaluronate fibers having a diameter of 0.3 to 5 μm, which are produced by electrospinning using a solvent of purified water alone.

[0029] From another viewpoint, the present invention relates to a hyaluronate nanofabric sheet having a transdermal absorbency of 77.70 to 86.08% and a tensile strength of 5.32 to 10.91 MPa.

[0030] The hyaluronate constituting the hyaluronate nanofabric sheet has a weight average molecular weight of 5×10 3 ~5×10 4 Da hyaluronate salt 88.9-98.1 wt% and weight average molecular weight 1×10 5 ~1×10 6 The composition is characterized by being composed of 1.9 to 11.1 wt % of hyaluronate of Da.

[0031] In other words, the hyaluronate nanofabric sheet of the present invention is characterized in that it is used in combination with hyaluronate, which has a medium molecular weight, to form the skeleton of the sheet, since hyaluronic acid, which has an ultra-low molecular weight, alone cannot form a sheet with high physical properties through electrospinning.

[0032] In the present invention, the molecular weight of the hyaluronate corresponding to the ultra-low molecular weight is 5×10 3 ~5×10 4 The molecular weight of hyaluronate, which is a medium molecule, is 1×10 Da. 5 ~1×10 6 It's Da.

[0033] Molecular weight 5×10 3 ~5×10 4 If the hyaluronic acid content of Da is less than 88.9% by weight, the sheet will not be produced or the transdermal absorption rate will be reduced, and if it exceeds 98.1% by weight, a sheet will be formed, but there is a problem that physical properties such as tensile strength will be reduced.

[0034] In the present invention, the hyaluronate is a salt bound to hyaluronic acid, and examples thereof include sodium hyaluronate, calcium hyaluronate, potassium hyaluronate, etc., but are not limited to these.

[0035] From another viewpoint, the present invention provides a method for producing a polymer having a weight average molecular weight of 5×10 3 ~5×10 4 Da hyaluronate and weight-average molecular weight 1×10 5 ~1×10 6 The present invention relates to a method for producing a hyaluronate nanofabric sheet, comprising the steps of (a) mixing a hyaluronate having a molecular weight of 1000 to 15000 Da with a hyaluronate having a molecular weight of 10000 Da and dissolving the mixture in water to produce an aqueous solution of the hyaluronate, and (b) electrospinning the aqueous solution of the hyaluronate.

[0036] In the present invention, the weight average molecular weight is 5×10 3 ~5×10 4 Da of hyaluronic acid and weight-average molecular weight of 1×10 5 ~1×10 6 The weight ratio of Da to hyaluronic acid is preferably 88.9-98.1% by weight:1.9-11.1% by weight.

[0037] In the present invention, the viscosity of the hyaluronic acid solution in which ultra-low molecular weight and medium molecular weight hyaluronic acid are mixed is preferably 1,000 to 15,000 cPs (25°C) (Brookfield DV2RTVJO, Spindle No. 5, rpm 12). The viscosity of the solution varies depending on the HA molecular weight (Da), HA content, and ratio with the solvent, but if the viscosity is less than 1,000 cPs, it is difficult to form a sheet, and if it exceeds 15,000 cPs, it is highly viscous and there is a risk that the nozzle will be clogged and electrospinning will not be performed smoothly.

[0038] In the present invention, the electrospinning is preferably carried out under the conditions of a tension of 30 to 35 (kV), a flow rate of 10 to 20 (mL / h), and a distance of 10 to 15 (cm).

[0039] In the present invention, the hyaluronate nanofabric sheet produced by electrospinning can be composed of hyaluronate fibers having a diameter of 0.3 μm to 5 μm.

[0040] In the present invention, the solvent is for dissolving the hyaluronate, and it is preferable to use purified water.

[0041] In addition, in the case of producing a hyaluronate nanofabric sheet by electrospinning used in the present invention, hyaluronic acid alone can be produced, but depending on the field of application, water-soluble, low molecular weight carrier or excipient components commonly used in the art can be further included, and the type and content range of the carrier or excipient components are not particularly limited. EXAMPLES

[0042] The present invention will be described in more detail below with reference to examples. It will be obvious to those skilled in the art that these examples are merely for illustrating the present invention and are not intended to limit the scope of the present invention.

[0043] Example 1: Preparation of hyaluronate nanofabric sheet by electrospinning Using an electrospinning device (NE300, Inovenso Co., Turkey), the tension, flow rate, and distance were set as shown in Table 1 below, and spinning was performed by changing the conditions of the molecular weight of the hyaluronate and the aqueous solution concentration.

[0044] [Table 1]

[0045] * Viscosity values ​​were measured at 12 rpm, 30 sec, and 25°C using a viscometer (DV2TRV TJO, Brookfield Engineering Labs Inc., USA). From Table 1, it was confirmed that sheets with molecular weights of 5 kDa to 50 kDa can be produced by electrospinning, and it was found that sheets ranging from high-physical properties nanofiber sheets to sheets with weak physical properties containing some dots can be produced depending on the concentration or molecular weight of the hyaluronate (Figure 1).

[0046] <Example 2: Preparation of hyaluronate nanofabric sheet by electrospinning> Using the hyaluronate aqueous solution with the composition shown in Table 2, electrospinning was carried out in the same manner as in Example 1 under the conditions of a tension of 30 kV, a flow rate of 10 to 30 mL / h, and a distance of 10 to 15 cm.

[0047] [Table 2]

[0048] From Table 2, 5 × 10 3 Da, 1 × 10 4 Da, and 5 x 10 4 Hyaluronate salt with a weight average molecular weight of 5×10 Da was used alone or 3 ~5×10 4 The content of hyaluronate of Da is 88.9 to 98.1% by weight, and the weight-average molecular weight is 1 × 10 5 ~1×10 6 It was found that the formation of a hyaluronate nanofabric sheet was possible when the content of Da hyaluronate was 1.9-11.1 wt % and the viscosity of the solution was 1,000-15,000 cPs.

[0049] <Experimental Example 1. Confirmation of the microstructure of hyaluronate nanofabric sheet> The microstructure of the electrospun hyaluronate nanofabric sheet was confirmed using a microscope (CX33RTFS2, Olympus Corporation., Korea) (Figure 1). In the case of the hyaluronate nanofabric sheet, either high-physical properties of nanofibers (Example 2-4) or low-physical properties of dot structures (Examples 2-6 and 2-11) were observed depending on the molecular weight and concentration of the hyaluronate.

[0050] <Experimental Example 2. Evaluation of percutaneous absorption rate and measurement of tensile strength> The percutaneous absorption rate evaluation test was conducted using a Franz diffusion cell (effective area: 0.64 cm) based on the "Guidelines for skin absorption tests in living organisms." 2 The skin permeation test was carried out under sink conditions using a device (Logan Instruments, New Jersey, USA) (receptor chamber volume: 5 mL).

[0051] Phosphate buffered saline (PBS) at pH 7.4 was used as the receptor phase for the skin permeation test. The epidermis layer (1.5cm x 1.5cm) of the prepared human skin was placed on the receptor chamber with the stratum corneum facing upwards, and the donor chamber was covered and fixed with a clamp. The receptor phase was then filled into a Franz diffusion cell, which was maintained at 32±1℃, and 100μL of the hyaluronic acid sheet solution was constantly applied to the donor site to perform the permeation test. After 1, 3, 6, 9, 12, and 24 hours of the permeation test, 5ml of the receptor phase was collected and analyzed, and replenished with fresh phosphate buffered saline.

[0052] For further qualitative analysis, the methods of Fudala, Rafal, et al. and deBelder, Anthony N. et al. (Photobiology B: Biology 104.3 (2011), Carbohydrate Research 44.2 (1975)) were referred to, and a fluorescence microscope was used to confirm that the hyaluronic acid nonwoven fabric (Example 2-4) permeated the skin over a 3-hour period under the same permeation test conditions (FIG. 2).

[0053] In the case of measuring tensile strength, the hyaluronate sheet prepared in Example 2 was measured for tensile strength, and the results are shown in Table 3. The tensile strength was measured by attaching a sample having a length of 15 cm and a width of 2.5 cm to a test fixture and setting the crosshead speed to 2 mm / min using a universal material testing machine.

[0054] [Table 3]

[0055] 5×10 3 Da, 1 × 10 4 Da, or 5 × 10 4 The percutaneous absorption rate of the hyaluronate nanofabric sheet produced using Da hyaluronate alone is high at 87.34-92.81%, but the measured tensile strength is 2.14-3.08 MPa, which means that the physical properties are poor, and there is a problem that the sheet is damaged during post-processing such as punching and packaging. In contrast, the percutaneous absorption rate of the hyaluronate nanofabric sheet produced by mixing ultra-low molecular weight and medium molecular weight hyaluronate is 77.70-86.08%, and the measured tensile strength is 5.32-10.91 MPa, which means that not only the percutaneous absorption rate but also the physical properties are excellent, and it can be usefully used as a mask patch for topical skin preparations and a carrier for ophthalmic or mucosal drug delivery systems.

[0056] In particular, it was confirmed that the lower the molecular weight of the mixed polymeric hyaluronate, the higher the transdermal absorption rate, but the lower the tensile strength.

[0057] Although the specific parts of the present invention have been described in detail above, it is clear to those skilled in the art that such specific descriptions are merely preferred embodiments and do not limit the scope of the present invention. Therefore, the substantial scope of the present invention is defined by the appended claims and their equivalents. [Industrial Applicability]

[0058] The hyaluronate nanofabric sheet of the present invention also has excellent mechanical properties, making it applicable to a variety of uses, such as a mask patch for topical skin preparations and a carrier for ophthalmic or mucosal drug delivery systems.

Claims

1. A hyaluronate nanofabric sheet consisting of hyaluronate fibers with a diameter of 0.3 to 5 μm produced by electrospinning using a solvent of purified water alone.

2. A hyaluronate nanofabric sheet having a transdermal absorption rate of 77.70 to 86.08% and a tensile strength of 5.32 to 10.91 MPa.

3. The hyaluronic acid salt has a weight average molecular weight of 5×10 3 ~5×10 4 88.9 to 98.1% by weight of hyaluronate having a molecular weight of 1×10 Da 5 ~1×10 6 The hyaluronate nanofabric sheet according to claim 2, characterized in that it is composed of 1.9 to 11.1 wt% of hyaluronate of Da.

4. The hyaluronate nanofabric sheet according to claim 2, characterized in that it is used as a mask patch for topical skin preparations, or a carrier for ophthalmic or mucosal drug delivery systems.

5. (a) Weight average molecular weight 5×10 3 ~5×10 4 Da hyaluronate and weight average molecular weight 1×10 5 ~1×10 6 and dissolving the mixture in water to prepare an aqueous solution of hyaluronate; (b) electrospinning an aqueous solution of hyaluronate.

6. Weight average molecular weight 5×10 3 ~5×10 4 Da hyaluronate and weight average molecular weight 1×10 5 ~1×10 6 The method for producing a hyaluronate nanofabric sheet according to claim 5, characterized in that the weight ratio of Da to hyaluronate is 88.9 to 98.1% by weight:1.9 to 11.1% by weight.

7. The method for producing a hyaluronate nanofabric sheet according to claim 5, characterized in that the viscosity of the hyaluronate aqueous solution is 1,000 to 15,000 cPs.

Citation Information

Patent Citations

  • Patches and percutaneous absorption-promoting agent of non-steroidal Anti-inflammatory agent

    JP2016155779A

  • Nanofiber matrices made of natural polymers with natural functional ingredients for cosmetics

    JP2023502305A

  • Electrospinning of natural polymers

    JP2023513376A

  • Nanofibrous sheet comprising hyaluronic acid and nanofibrous scaffold for enhanced tissue regeneration using the same

    KR1020110116616A

  • Method Of Producing Hyaluronic Acid Non Woven Fabric

    KR102338355B1